KÜÇÜK ve ORTA BOY İŞLETMELERDE (KOBİ’LERDE) ÜRÜN YENİLİĞİ ve AR-GE FAALİYETLERİ - Erdil, Oya; İmamoğlu, Salih Zeki; Keskin, Halit (Marmara Üniversitesi, 2003)
This study analyses product innovation and research and development (R&D) activities of small and medium sized enterprises (SMEs). A conceptual analysis has been conducted based on the literature on SMEs, innovation and product innovation in SMEs. An investigation on a sample of SMEs operating in production sector has been held in order to draw conclusions on R&D activities of the firms in the sample. The data has been gathered by a questionnaire form including questions under the headings of R&D activities, institutions supplying R&D support and the nature of the support, restrictions of firms unabling them having various R&D supports, and R&D shares of the firms in their annual sales. Furthermore a chi-square analysis has been utilized in order to evaluate relationship between R&D operations and product development and radical product innovation. Based on in-depth interviews with firm representatives and questionnaire forms gathered from them and a review of the literature the present research discusses the implications of the results and suggestions for practitioners and scholars for further research are proposed.